Comparison of Long-term Outcomes of Infliximab versus Adalimumab Treatment in Biologic-Naïve Patients with Ulcerative Colitis - Lee, Yong Il (Gut Liver, 2021)
BACKGROUND/AIMS: The tumor necrosis factor-α inhibitors infliximab and adalimumab are standard treatments for moderate to severe ulcerative colitis (UC). However, there has been no head-to-head comparison of treatment efficacy and outcomes between the two agents. The aim of this study was to compare the efficacy and long-term outcomes of infliximab versus adalimumab treatment in biologic-naïve patients with UC. METHODS: We retrospectively analyzed the records of 113 biologic-naïve patients with UC who were treated between September 2012 and December 2017 (the infliximab group [n=83] and the adalimumab group [n=30]). We compared remission and response rates between these groups at 8 and 52 weeks. We used Kaplan-Meier curves to compare long-term outcomes, and logistic regression analysis and Cox-proportional hazard regression models to assess factors affecting outcomes. RESULTS: The median follow-up duration was 25.8 months. Baseline clinical characteristics were similar between groups. There were no significant differences between the two groups in the rate of clinical remission or clinical response at 8 or 52 weeks. Multivariate analyses also showed that long-term outcomes were not significantly different (adjusted hazard ratio [HR], 1.45; 95% confidence interval [CI], 0.81 to 2.56; p=0.208). An elevated C-reactive protein level (greater than 5 mg/L) was a significant predictive factor for poor outcomes (adjusted HR, 2.25; 95% CI, 1.37 to 3.70; p=0.001). During the follow-up period, the rates of adverse event were not significantly different between the two groups (p=0.441). CONCLUSIONS: In our study, infliximab and adalimumab had similar treatment efficacy and long-term outcomes in biologic-naïve patients with moderate to severe UC.